2007
DOI: 10.1111/j.1747-0765.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of salt glands in Rhodes grass (Chloris gayanaKunth) to secrete Na+and K+

Abstract: Some plants are able to tolerate salinity using salt glands on the leaf surface, which secrete excess salts transported into the leaves. Rhodes grass (Chloris gayana Kunth) reportedly possesses such salt glands, but the features of secretion remain unclear. In the present study, we compared the ability of Rhodes grass salt glands to secrete sodium and potassium with the aim of clarifying the preference of cations for secretion. In both whole plant experiments and detached leaf experiments, NaCl treatment incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
3
23
1
Order By: Relevance
“…As shown in Figures 3 and 6, the proportions of Na + and K + accumulated in plant tissues of T. ramosissima were 3.67 and 11.04, respectively, and those of T. laxa were 3.06 and 8.43, respectively (Figures 3 and 6); this indicates that the Tamarix species had a higher affinity to K + , which led to decreased K + secretion. Similar results have been reported in previous studies on Sporobolus spicatus and Rhodes grass [6,10].…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…As shown in Figures 3 and 6, the proportions of Na + and K + accumulated in plant tissues of T. ramosissima were 3.67 and 11.04, respectively, and those of T. laxa were 3.06 and 8.43, respectively (Figures 3 and 6); this indicates that the Tamarix species had a higher affinity to K + , which led to decreased K + secretion. Similar results have been reported in previous studies on Sporobolus spicatus and Rhodes grass [6,10].…”
Section: Figuresupporting
confidence: 93%
“…After detection, it was found that the total ATPase level in the plasma of the secreting cells was four-fold that of the mesophyll cells, and the activity of the former was more sensitive to the mitochondrial inhibitor Na-azide and plasma membrane inhibitor Vanadate; therefore, it was further deduced that H + -ATPase played an important role in the ion secretion. Kobayashi [10] found that the bicellular salt glands of Rhodes grass showed higher ability to secrete Na + than K + , and that the plasma membrane H + -ATPase inhibitors, ion channel inhibitors, Na + -K + -ATPase inhibitors, and Ca 2+ and K + channel inhibitors had different effects on Na + and K + secretion; these findings indicated that the preferential Na + secretion in salt glands might be due to the different secretory channels for different ions. The results of recent research showed that ion secretion of multicellular salt glands was regulated by several salt gland inhibitors, such as proton pump inhibitors, Ca + pump inhibitors and K + channel inhibitors [9][10][11][12][13].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Norin 61) was cultivated in accordance with our previous report (Kobayashi et al 2007) with modifications. Plants were cultivated in a growth chamber with an air temperature of 25/20°C (12-h day/12-h night cycle).…”
Section: Growth Conditions and Hormone Treatmentmentioning
confidence: 99%